Environmental conditions, not sugar export efficiency, limit the length of conifer leaves. (30th May 2018) - Han, Xiaoyu; Turgeon, Robert; Schulz, Alexander; Liesche, Johannes
Abstract: Most conifer species have needle-shaped leaves that are only a few centimeters long. In general, variation in leaf size has been associated with environmental factors, such as cold or drought stress. However, it has recently been proposed that sugar export efficiency is the limiting factor for conifer needle length, based on the results obtained using a mathematical model of phloem transport. Here, phloem transport rates in long conifer needles were experimentally determined to test if the mathematical model accurately represents phloem transport. The validity of the model's assumptions was tested by anatomical analyses and sugar quantification. Furthermore, various environmental and physiological factors were tested for their correlation with needle length. The results indicate that needle length is not limited by sugar transport efficiency, but, instead, by winter temperatures and light availability. The identification of factors that influence needle size is instrumental for using this trait as a variable in breeding programs.